La historia de los perdedores en el teatro de Luis Enrique Gutierrez Ortiz Monasterio - Daniel Vázquez Touriño (Études romanes de Brno, 2013)
This paper introduces two recent plays by Mexican playwright Luis Enrique Gutiérrez Ortiz Monasterio: Presidio y muerte de Don Guillén de Lampart and Cayendo con Victoriano. Both of them deal with the significant processes of Mexican history which were widely commemorated during the year 2010: the independence from Spain and the Revolution. The aim of this article is to show how, thanks to certain postdramatic and narrative aspects of the texts, both main characters –a hero (Lampart) and a villain (Huertas)– are presented in a very less "black and white" way than traditionally, and, even more important, how this theatre claims that the importance of history resides in the reflexion that produces on today's audience.